Quantitative Proteomic Profiling of Mitochondrial Toxicants in a Human Cardiomyocyte Cell Line - Wei, Zhengxi; Zhao, Jinghua; Niebler, Jake; Hao, Jian-Jiang; Merrick, B. Alex; Xia, Menghang (Frontiers in Genetics, 2020)
Mitochondria are essential cellular organelles that participate in important cellular processes, including bioenergetics, metabolism, and signaling. Recent functional and proteomic studies have revealed the remarkable complexity of mitochondrial protein organization. Protein machineries with diverse functions such as protein translocation, respiration, metabolite transport, protein quality control and the control of membrane architecture interact with each other in dynamic networks. The goal of this study was to identify protein expression changes in a human cardiomyocyte cell line treated with several mitochondrial toxicants which inhibit mitochondrial membrane potential (MMP) and mitochondrial respiration. AC16 human cardiomyocyte cells were treated with carbonyl cyanide p-(trifluoromethoxy) phenylhydrazone (FCCP), dinoterb, picoxystrobin, pinacyanol and triclocarban for 18 h around the IC50 values generated from MMP assay. The samples were harvested and labeled with tandem mass tags with different mass isotopes. Peptide assignment was performed in Proteome Discoverer. Each dataset was analyzed in Ingenuity Pathway Analysis (IPA). In the proteomic profile, these compounds showed dysregulation of a group of mitochondrial proteins (e.g. NDUA, NDUB, BCS1, CYB5B and SDHF2), as well as proteins involved in lipid metabolism (e.g. CPT, MECR, and LPGAT1), cytoskeleton protein changes (e.g. CROCC, LAMC3, FBLN1 and FMN2) and stress response (e.g. IKBKG, IKBB, SYVN1, SOD2 and CPIN1). Proteomic data from the current study provides key insights into chemical induced cellular pathway dysregulation, supporting the use of proteomic profiling as a sensitive method to further explore molecular functions and disease pathogenesis upon exposure to environmental chemicals.